2014
DOI: 10.1111/jhn.12197
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of body composition measurement techniques

Abstract: The data indicate that ADP and BIA cannot be used interchangeably, although both measurements had good within- and between-day agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…Strong Spearman correlation coefficients were found between FM% ADP and FM% BIA , especially in girls, in accordance with previous studies . Similar results were found based on ICC: good exchangeability in girls but inadequate exchangeability in boys.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Strong Spearman correlation coefficients were found between FM% ADP and FM% BIA , especially in girls, in accordance with previous studies . Similar results were found based on ICC: good exchangeability in girls but inadequate exchangeability in boys.…”
Section: Discussionsupporting
confidence: 91%
“…FM% BIA did not result in an overall significant difference but overestimated and underestimated FM% in children with lower and higher FM% respectively. Other studies found significant overall differences for FM% BIA : an underestimation using another HtF BIA in adults and an FtF BIA in children and an overestimation in adults using the same HtF as ours …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations